Les projets de restauration écologique en question : expérimenter un trajet d’instauration sur le fleuve Rhône avec Souriau - Yves-François Le Lay; Fanny Reymond; Emeline Comby; Marylise Cottet; Clotilde Lebreton; Jean-Michel Olivier; Jérémie Riquier (VertigO)
Although the development of the Rhône River was intended to protect against flooding, to produce hydroelectricity, to facilitate navigation and to irrigate crops, it also had negative hydrological, geomorphological, and ecological consequences. To mitigate these, a ten-year program of hydraulic and ecological restoration of the river was launched in 1998. This article aims to critically evaluate the idea of ecological restoration through the philosophical approach proposed by Souriau. After presenting the salient points of his reflections, we develop the case of the island of La Platière, at the limit of three French departments (Ardèche, Isère, and Loire), by detailing the results of a survey that focused on the way this space is inhabited and on the works envisaged to revitalize the functioning of the Rhône River. While the people interviewed recognize the hybridity of the aquatic and terrestrial ecosystems, their comments reveal not only that they remain attached to them but also that the situation could be improved. Thus, the inhabitants could actively contribute to efforts to give the river more autonomy. Souriau's work provides a solid theoretical framework for recent developments in the revitalization of the Rhône River, which are more the results of the trial and error inherent in real-life experimentation than with the scrupulous respect for all the steps imposed by a restoration project blind to the particularities of local and concrete situations.